Sexuality in subjects with intellectual disability: an educational intervention proposal for parents and counselors in developing countries La sexualidad en personas con discapacidad intelectual: una propuesta de intervención educacional para padres y consejeros en paises en desarrollo - Gregorio Katz; Eduardo Lazcano-Ponce (Instituto Nacional de Salud Pública, 2008)
In developing countries, the study of intellectual disability has enormous knowledge gaps, especially in the areas of intervention, utilization of services and legislation. This article provides information not only for aiding in the potential development of sexuality in individuals with intellectual disability, but also for fostering their social integration. In Mexico and the region, in order to develop educational interventions for promoting sexual health, it is necessary to consider the following priorities: a) mental health professionals should have the knowledge or receive training for carrying out a sexual education and counseling program; b) educational interventions for subjects with intellectual disability should be adapted for the different stages of life (childhood, adolescence and adulthood); c) during childhood, educational intervention should emphasize the concept of public and private conducts; d) in adolescence, intervention should consider the actual mental age and not the chronological age of the subjects receiving intervention; e) the expression of sexuality in the adult with intellectual disability depends on the early incorporation of factors for promoting social inclusion; f) for educational interventions to be successful, it is fundamental that sexual educators and counselors, in addition to working with the clients, also work with their parents and other close family members; g) intervention programs should establish development objectives for developing in persons with intellectual disability a positive attitude towards sexuality and the improvement in self-esteem; h) in subjects with intellectual disability, their linguistic comprehension level should be taken into consideration and techniques for open discussion and non-inductive education should be used; i) social integration programs should address the needs of developing countries and their individuals, since it is not feasible to import external programs due to differences in infrastructure and the absence of public policies for promoting development; j) full sexuality in subjects with intellectual disability should be fostered in a comprehensive manner within an independent living program; k) in Mexico and the region, public policies should be instituted for administering independent living programs for people with intellectual disability and should lead to social, familial and economic power for the purpose of being productive. Thus, people with mental deficiency in developing countries can aspire to being integrated into social and work life and to appropriately expressing their sexuality. El estudio de la discapacidad intelectual presenta enormes lagunas de conocimiento en los países en desarrollo, sobre todo en las áreas de intervención, utilización de servicios y legislación. Este artículo proporciona información no sólo para contribuir al desarrollo potencial de la sexualidad en los individuos con discapacidad intelectual, sino también para impulsar su integración social. A fin de poder desarrollar intervenciones educativas para la promoción de la salud sexual en México y en la región, hay que considerar las siguientes prioridades: a) los profesionales de la salud mental deben tener los conocimientos o recibir capacitación a fin de poder llevar a cabo un programa de asesoramiento y educación sexual; b) las intervenciones educativas para los individuos con discapacidad intelectual deben estar adaptadas a las distintas etapas de la vida (infancia, adolescencia y edad adulta); c) durante la infancia, la intervención educativa debe enfatizar el concepto de conductas pública y privada; d) en la adolescencia, la intervención debe tomar en cuenta la edad mental real y no la edad cronológica de los individuos que reciben intervención; e) la expresión de la sexualidad en el adulto con discapacidad intelectual depende de la previa incorporación de factores promotores de inclusión social; f) para que las intervenciones educativas tengan éxito, es esencial que los educadores y asesores en lo sexual, además de trabajar con los clientes, trabajen también con sus padres y con otros miembros cercanos de la familia; g) los programas de intervención deben establecer objetivos de desarrollo para la creación de actitudes positivas hacia la sexualidad y una mejora en la autoestima de las personas con discapacidad intelectual; h) en los individuos con discapacidad intelectual se debe tomar en cuenta su nivel de comprensión lingüística y se deben utilizar técnicas para discusión abierta así como educación no inductiva; i) los programas de integración social deben adecuarse a las necesidades de los países en desarrollo y sus individuos, ya que no es posible importar programas del exterior debido a las diferencias en infraestructura y a la ausencia de políticas públicas para promover el desarrollo; j) se deberá promover ampliamente una sexualidad integral en los individuos con discapacidad intelectual dentro de un programa de vida independiente; k) tanto en México como en la región deberán instaurarse políticas públicas para la administración de programas de vida independiente para personas con discapacidad intelectual que proporcionen el poder social, familiar y económico que les permita ser productivas. De esta manera las personas con deficiencias mentales en los países en desarrollo podrán aspirar a la integración social y laboral y a expresar apropiadamente su sexualidad.